Peritoneal Dialysis in Children with Acute Kidney Injury: Dhaka Shishu (Children) Hospital Experience - Sarker, NK; Hanif, M; Rouf, MA; Sarkar, PK; Mahmud, S; Setu, M; Khondaker, T (Anwer Khan Modern Medical College Journal, 2017)
Background: The choices for renal replacement therapy (RRT) in children with acute kidney injury (AKI) are limited in developing countries. Peritoneal dialysis (PD) is the preferred and convenient treatment modality for acute kidney injury (AKI) in children and hemodynamically unstable patients. Methods: This is a cross sectional descriptic type of observational study of children who underwent PD for AKI in 43 children (27 boys) in nephrology department of Dhaka Shishu (children) Hospital from January 2013 to December 2013. Result: The study included 43 children (62.8 % male). Mean age was 2 ± 1.07 years, with the youngest being 2 months, and the oldest, 14 years. Most common causes was septicaemia (25.6%) and hypovolumia (25.6%) followed by unknown etiology (16.2%), glomerulonephritis (11.6%), wasp sting (9.3%) and hemolytic uremic syndrome (7%). Overall mortality was 32.5%, most common in unknown etiology and high in male but not statistically significant (p=0.42). Conclusions: In the developing countries, PD can be successfully performed for the management of childhood AKI. Septicaemia and hypovolumia are the leading causes of AKI, however mortality higher in male and unknown etiology. Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 11-14